Fifty years of capital markets research in accounting: Achievements so far and opportunities ahead - Ilia D. Dichev (China Journal of Accounting Research, 2020)
This paper reviews the literature on capital markets research in accounting over the last 50years. Rather than trying to be comprehensive, the review focuses on selected areas, and strives to be forward-looking. The first major takeaway is that the literature has made great progress, especially on the technical side. The second takeaway is that great opportunities remain, especially in using Big Data, looking more closely into the accrual process, and in issues related to standard setting.
Keywords: 650